Lucio Phenomenon: An Unusual Case of Skin Necrosis - Kaveri Rusia; Vikrant Saoji; Bhushan Madke; Adarshlata Singh (Case Reports in Dermatology, 2024)
Introduction: Lucio leprosy is a non-nodular diffuse type of lepromatous leprosy first described by Lucio and Alvarado. Lucio phenomenon is a rare vasculonecrotic reaction characterized by cutaneous necrosis with minimal constitutional features. Case Presentation: We describe an unusual case of a 53-year-old man from Central India who had blisters, ulcers, and widespread erosions on his foot, forearms, and arms. The diagnosis of lepromatous leprosy with the Lucio phenomenon was established after thorough evaluation by clinical findings, histopathological findings, and slit-skin smear examination. Conclusion: Lucio phenomenon is an uncommon cause of cutaneous infarction and necrosis. Primary care physicians should keep a high index of suspicion in patients with cutaneous necrosis and minimal constitution features. Since leprosy is a relatively curable disease, primary care physicians should think of a rare form of lepromatous leprosy presenting with cutaneous necrosis, especially in non-endemic zones.